2022
DOI: 10.1039/d2nj03189b
|View full text |Cite
|
Sign up to set email alerts
|

An acid-catalyzed polyol in situ crosslinked alginate ester/Antarctic krill protein composite fiber with improved strength and water resistance

Abstract: Alginate-based fiber with good biocompatibility and non-immunogenicity has a wide application in biomedical materials. However, low strength and poor water resistance still limit the application in tissue engineering materials. In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In addition, all composite films exhibited new peaks at 2 θ = 34.4° ( d -spacing = 0.26 nm) and 39.8° ( d -spacing = 0.23 nm), which were achieved by thermal shearing and solvent post-treatment, indicating that electrostatic interactions and hydrogen bonding between CS and SP might contribute to the crystalline structure . It was reported that the greater the force between chitosan, the more it could affect the crystallization ability of molecular chains. , The resultant higher degree of crystallinity might be beneficial to the tensile strength of the composite films (Table S1).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, all composite films exhibited new peaks at 2 θ = 34.4° ( d -spacing = 0.26 nm) and 39.8° ( d -spacing = 0.23 nm), which were achieved by thermal shearing and solvent post-treatment, indicating that electrostatic interactions and hydrogen bonding between CS and SP might contribute to the crystalline structure . It was reported that the greater the force between chitosan, the more it could affect the crystallization ability of molecular chains. , The resultant higher degree of crystallinity might be beneficial to the tensile strength of the composite films (Table S1).…”
Section: Resultsmentioning
confidence: 95%
“…24 It was reported that the greater the force between chitosan, the more it could affect the crystallization ability of molecular chains. 46,47 The resultant higher degree of crystallinity might be beneficial to the tensile strength of the composite films (Table S1).…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 99%
“…188 Various techniques utilizing multiple cross-linking networks have been employed to produce robust hydrogel fibers. 37,189 Drawing inspiration from this, the aim is to create gel fibers with improved mechanical toughness and strength by introducing intermolecular-linking networks. Hence, there is a strong need to create an effective method for manipulating molecular networks within gel fibers to enhance their overall mechanical performance.…”
Section: Twisting/spiral Architecture and Crosslinkingmentioning
confidence: 99%
“…Various techniques utilizing multiple cross‐linking networks have been employed to produce robust hydrogel fibers 37,189 . Drawing inspiration from this, the aim is to create gel fibers with improved mechanical toughness and strength by introducing intermolecular‐linking networks.…”
Section: Strengthening Strategies For Mechanically Strong Fibersmentioning
confidence: 99%
“…Alginate‐based fibers with good biocompatibility and non‐immunogenicity demonstrate wide applications in biomedical materials. Xu et al 109 reported an alginate ester/Antarctic krill protein (AE/AKP) composite fiber with a covalent cross‐linked and hydrogen‐bonded structure was synthesized on the basis of the acid‐catalyzed phase separation reaction spinning. By using sodium alginate as the matrix, cytotoxicity test results revealed that the fiber exhibits nontoxicity.…”
Section: Strategies For the Fabrication Of Tough Hydrogelsmentioning
confidence: 99%